2009
DOI: 10.1016/j.ygyno.2008.08.030
|View full text |Cite
|
Sign up to set email alerts
|

Cost effectiveness of high-risk HPV DNA testing for cervical cancer screening in South Africa

Abstract: a b s t r a c t a r t i c l e i n f oObjective. To determine the cost effectiveness of several cervical cancer screening strategies utilizing HPV testing in South Africa.Methods. We developed a lifetime Markov model of the costs, quality of life, and survival associated with screening and treating cervical cancer and its precursors. Screening strategies evaluated included: 1) conventional cytology, 2) cytology followed by HPV testing for triage of equivocal cytology, 3) HPV testing, 4) HPV testing followed by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
48
0
3

Year Published

2010
2010
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 44 publications
(53 citation statements)
references
References 45 publications
2
48
0
3
Order By: Relevance
“…Methods for calculating the ICER in six articles were; cost/ QALY (Mandelblatt et al, 2002b, Berkhof et al, 2010Chuck, 2010;Chow et al, 2010;Vijayaraghavan et al, 2009;2010a), in 13 studies the ICER were estimated by cost/LYG (Brown and Garber, 1999;Maxwell et al, 2002;Mandelblatt et al, 2002a;Goldie et al, 2001;2004;Kim et al, 2005;Bidus et al, 2006;Andres-Gamboa et al, 2008;Kulasingam et al, 2009;Levin et al, 2010;Sroczynski et al, 2011;Burger et al, 2012). Two studies did not report their ICER (Bistoletti et al, 2008;de Kok et al, 2012).…”
Section: Results By Outcomesmentioning
confidence: 99%
See 4 more Smart Citations
“…Methods for calculating the ICER in six articles were; cost/ QALY (Mandelblatt et al, 2002b, Berkhof et al, 2010Chuck, 2010;Chow et al, 2010;Vijayaraghavan et al, 2009;2010a), in 13 studies the ICER were estimated by cost/LYG (Brown and Garber, 1999;Maxwell et al, 2002;Mandelblatt et al, 2002a;Goldie et al, 2001;2004;Kim et al, 2005;Bidus et al, 2006;Andres-Gamboa et al, 2008;Kulasingam et al, 2009;Levin et al, 2010;Sroczynski et al, 2011;Burger et al, 2012). Two studies did not report their ICER (Bistoletti et al, 2008;de Kok et al, 2012).…”
Section: Results By Outcomesmentioning
confidence: 99%
“…Chuck et al remarked that Pap smear screening every three years for all Canadian women and HPV triage for women older than 30 years with ASCUS were the most cost-effective strategies (Chuck, 2010 (Maxwell et al, 2002;Bidus et al, 2006). Berkhof et al (2010) in the Netherlands, indicated that starting screening with HPV triage with 5 years interval was the most cost effective strategies (Berkhof et al, 2010).Vijayaraghavan in South Africa reported that coscreening with HPV testing was less costly and the most effective strategy (Vijayaraghavan et al, 2009). Based on income we just found 5 articles in high income countries suggested starting age of screening below age 30 (Mandelblatt et al, 2002b;Kulasingam et al, 2009;Chuck, 2010;Vijayaraghavan et al, 2010a;Sroczynski et al, 2011)(Table1).…”
Section: Comparison Of Starting Age Of Screeningmentioning
confidence: 99%
See 3 more Smart Citations